Survival, reproduction, avoidance behavior and oxidative stress in the earthworm Octolasion cyaneum exposed to glyphosate - Salvio, Carla; Menone, Mirta Lujan; Rafael, Sergio; Iturburu, Fernando Gastón; Manetti, Pablo (2018)
The massive use of glyphosate (GLY) in several countries has increased the interest in investigating its potential adverse effects in non-target organisms. The aim of the present study was to assess the potential effects in survival and reproduction; avoidance behavior and oxidative stress under short-term (48 h) and subchronic exposures (28 days) to GLY in the earthworm Octolasion cyaneum. After 48 h no significant changes in the behavior was observed. In addition, a lower catalase activity at 498 μg GLY kg−1 dry soil section relative to earthworms from the control section was obtained. After 28 days of exposure inhibition of glutathione S-transferase activity was observed at 535 μg GLY kg−1 dry soil while no changes in the other endpoints were detected. These results indicate that environmentally relevant concentrations of GLY (up to 996 µg GLY kg−1 dry soil) did not exert a toxic effect to O. cyaneum.